(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
After the collapse of the USSR, territorial and border disputes arose between the newly independent states of Central Asia, which were of an acute nature. Their causes go back to the Soviet past, during the period of the national-territorial delimitation of 1924-1927. The article examines the history of border-territorial relations on the example of the Kyrgyz Republic and the Republic of Tajikistan, which were of a tough nature.